A Comparison Between Disney Earlier and Recent Princess of The Third Generation of Disney Animated Films as Seen in Rapunzel in Tangled and Moana in Moana - Nastasha Primera Anindita (Institute of Research and Community Outreach - Petra Christian University, 2022)
This study compares the girl power characteristics such as bravery, independence, and intelligence in identifying Rapunzel as the earlier princess character and Moana as the recent princess character of the third generation of Disney Princesses in the two Disney Princess Animated Films titled Tangled and Moana. As a result of this study, I found that in terms of bravery, Moana as the recent princess, is more daring to make decisions and take risks when compared to Rapunzel as the earlier princess of the third generation. In terms of independence, it can also be seen that Rapunzel still seems to rely more on other people to help her find a way and protect herself, in contrast to Moana, who can find the destination by herself and work together with other people and make them become her partners. In terms of intelligence, both Rapunzel and Moana are good at managing their daily activities, but in terms of solving problems, Rapunzel still uses the power of magical stuff, unlike Moana, who uses all her mind and strength to solve the problems she faces.Keywords: girl power, bravery, independence, intelligence, characteristics